Supramolecular structures of NiII and CuII with the sterically demanding Schiff base dyes driven by cooperative action of preagostic and other non-covalent interactions. (2021) - Shiryaev, Alexey A.; Burkhanova, Tatyana M.; Mitoraj, Mariusz P.; Kukulka, Mercedes; Sagan, Filip; Mahmoudi, Ghodrat; Babashkina, Maria G.; Bolteg, Michael; Safin, Damir A.
No abstract available